Agricultural soft budget constraints in new European Union member states. Issue 1 (9th August 2019) - Fertő, Imre; Bojnec, Štefan; Fogarasi, József; Viira, Ants Hannes
Abstract: This article investigates farm investment behaviour and the presence of soft budget constraints in the agricultural sectors of three Central and Eastern European countries – Estonia, Hungary and Slovenia – using individual farm accountancy panel data for the 2007–2015 period. Gross farm investment is positively associated with gross farm investment for the previous year, growth in real sales and public investment subsidies. Mixed results for debt square and cash flow variables imply that the different investment behaviour of farms pertains to different structures of investment sources among the countries under analysis. A particularly significant negative cash flow coefficient implies strong soft budget constraints for Estonian farms, while insignificant cash flow coefficients imply weak soft budget constraints for Hungarian and Slovenian farms.